Optimization of the arc compressor performance in the MariX free electron laser. (July 2020) - Conti, M Rossetti; Bacci, A; Rossi, A R; Perillo, V; Serafini, L
Abstract: The MariX FEL is a compact GeV-class X-ray source exploiting a two-pass two-way acceleration in a Super-Conducting linac operated in continuous wave mode. A key component of this peculiar machine layout is the Bubble Arc Compressor (BAC), a 300 m long beamline consisting of 14 "Double Bend Achromat" cells and a bidirectional quadrupole focusing channel, which allows the beam to make a U-turn while it is being compressed to greatly increase its brightness and peak current. In this paper we present the performance of the BAC of MariX and the solutions we adopted to solve the main issues that the beam dynamics encounters in a line of this kind. We show the beam dynamics in the BAC matching line which is designed to operate on beams propagating in both directions, considering the anti-symmetric quadrupole focusing behavior. We study the Coherent Synchrotron Radiation (CSR) emission in the BAC showing a scheme that preserves the low emittance granting also a linear compression in presence of strong CSR effects. Lastly, we present a strategy to correct the residual dispersion-based beam tilt that is introduced by the CSR kick and would otherwise spoil the FEL emission. Further, the projected emittance is minimized cancelling the dispersive contributions.